'Know before you go': information-seeking behaviour of German patients receiving health services abroad in light of the provisions of Directive 2011/24/EU. (July 2015) - Panteli, Dimitra; Wagner, Caroline; Verheyen, Frank; Busse, Reinhard
Objective: While Directive 2011/24/EU on cross-border patient mobility makes specific provisions in relation to information availability and accessibility, little empirical evidence exists to guide best practice. This paper explores the information-seeking behaviour of German patients who received planned care abroad. Methods: A postal survey among German patients treated in other European countries was carried out by Techniker Krankenkasse, a major German sickness fund. The influence of certain predictors on whether patients informed themselves before travelling for care was investigated using multiple logistic regression. Types and sources of information were analysed using descriptive statistics. Results: Information activity was contingent on patients' level of education, type of service, regularity of treatment abroad and awareness of entitlement to cross-border services. Respondents most frequently enquired about elements of reimbursement, entitlement to services and cost-saving, and consulted their sickness fund for information. Differences in both content and medium of choice were observed between patient groups. Conclusion: A structured and inclusive approach to information provision should be adopted. National Contact Points should collaborate with a range of stakeholders, who will vary depending on the health care system; however, patient organizations, health professionals and third-party payers should always be represented. Dynamically monitoring cross-border movements can help determine the range, medium and language of relevant information.